Types of Code Switching in the Conversation between the Tour Guide and the Visitors at Fatahillah Museum Jakarta - Yuliasari, Ria; Virtianti, Rika; Sari, Ferdias Prihatna (Pujangga : Jurnal Bahasa dan Sastra, 2023)
ABSTRACTThe presence of social media has influenced the use of foreign languages, especially English, in daily communication, especially among Generation Y or the millennials. The use of foreign languages is very diverse, ranging from the use of technological terms such as download, print, copy and paste, to the combination of basic Indonesian words with English affixes such as pelukable and unfaedah. The merging of the two languages is known as code switching and code mixing. This study is aimed at analyzing the types of code switching uttered by a tour guide at the Fatahillah museum in Jakarta. Analysis of the type of code switching is done by using Hoffman's theory. The results showed that there were three types of code switching; tag swiching, inter-sentential swictching and intra-sentential switching. There were also eighteen code switching utterances in the conversation between the tour guide and the museum visitors. And of the eighteen utterances, the most common type of code switching is tag code switching. Keywords: code switching, types of code switching